2008
DOI: 10.1007/s00464-008-9888-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thoracic epidural analgesia on postoperative pain relief and ileus after laparoscopic colorectal resection

Abstract: TEA provides a significant benefit in terms of less analgesic consumption, better postoperative pain relief, and faster recovery of gastrointestinal function in patients undergoing laparoscopic colorectal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 28 publications
(47 reference statements)
1
70
1
5
Order By: Relevance
“…23 In two recent studies, a laparoscopic approach to colon resection, together with thoracic epidural local anesthetics, contributed to accelerate the return of bowel function and dietary intake. 14,15 This physiological benefit, however, did not translate into faster hospital discharge (median of 5 days). Such findings prompted us to consider the need to revise surgical and nursing management and allocation of resources.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…23 In two recent studies, a laparoscopic approach to colon resection, together with thoracic epidural local anesthetics, contributed to accelerate the return of bowel function and dietary intake. 14,15 This physiological benefit, however, did not translate into faster hospital discharge (median of 5 days). Such findings prompted us to consider the need to revise surgical and nursing management and allocation of resources.…”
Section: Discussionmentioning
confidence: 94%
“…Following are the main elements of the fast-track protocol, as proposed by Kehlet et al 9,10 : preoperative patient education; appropriate discharge planning; limited disruption of fasting period; attenuation of the surgical stress response by minimizing surgical incision and thoracic epidural blockade [11][12][13][14][15] ; optimization of postoperative pain relief by using multimodal analgesia; avoidance or early removal of drains and tubes; and earlier oral feeding and enforced mobilization. These authors have reported a reduction of hospital stay to 2-3 days, low readmission rate, and low morbidity.…”
Section: Résumémentioning
confidence: 99%
“…Zingg et al who studied the influence of TEA on postoperative pain relief and ileus after laparoscopic colorectal resection, he concluded that TEA provides a significant benefit in terms of less analgesic consumption, better postoperative pain relief [24].…”
Section: Resultsmentioning
confidence: 99%
“…First, this ERP did not incorporate several recommended ERP components, as they have only recently been reported. These components include oral carbohydrate loading [35], perioperative intravenous fluid restriction [36], epidural analgesia [37], and avoidance of mechanical bowel preparation (MBP) [38]. The goal-directed fluid management using pulmonary artery catheter or esophageal Doppler was not used in this study.…”
Section: Discussionmentioning
confidence: 99%